MEDULLARY THYROID CARCINOMA - V. S. Medvedev; P. A. Isayev; A. A. Ilyin; D. Yu. Semin; V. V. Polkin; D. N. Derbugov; S. V. Vasilkov (Опухоли головы и шеи)
Medullary thyroid carcinoma belongs to orphan diseases affecting a small part of the population. Multicenter trials are required to elaborate a diagnostic algorithm, to define treatment policy, and to predict an outcome.